Assessing the domestic and foreign Islamic banks efficiency: Insights from selected Southeast Asian countries - Fakarudin Kamarudin; Fadzlan Sufian; Foong Wei Loong; Nazratul Aina Mohamad Anwar (Future Business Journal, 2017)
The objective of this study is to examine the technical efficiency (TE) and the decomposition of pure technical efficiency (PTE) and scale efficiency (SE) of domestic and foreign Islamic banks from the selected Southeast Asian Countries. The sample comprised of 29 domestic and foreign Islamic banks from Malaysia, Indonesia and Brunei over the period of 2006-2014. This study employ the Data Envelopment Analysis (DEA) method to measure banks' efficiency. In addition, the parametric (t-test) and non-parametric (Mann-Whitney [Wilcoxon] and Kruskall-Wallis) tests also performed to examine the difference in the efficiency of the foreign and domestic Islamic banks. The results indicate that the domestic Islamic banks have exhibited higher efficiency levels compared to their foreign bank peers. In addition, the empirical findings from this study seem to suggest that the domestic Islamic banks have exhibited a higher efficiency levels for all three efficiency measures and consistent with home field advantage theory. The findings of this study are expected to contribute significantly to the regulators or policymakers, Islamic banking itself, investors and existing knowledge on the operating performance of the Islamic banking sector.
Keywords: 650; Brunei; Data envelopment analysis; Efficiency; Indonesia; Islamic banks; Malaysia